An open source cyberinfrastructure for collecting, processing, storing and accessing high temporal resolution residential water use data. (October 2021) - Bastidas Pacheco, Camilo J.; Brewer, Joseph C.; Horsburgh, Jeffery S.; Caraballo, Juan
Abstract: Collecting and managing high temporal resolution residential water use data is challenging due to cost and technical requirements associated with the volume and velocity of data collected. We developed an open-source, modular, generalized architecture called Cyberinfrastructure for Intelligent Water Supply (CIWS) to automate the process from data collection to analysis and presentation of high temporal residential water use data. A prototype implementation was built using existing open-source technologies, including smart meters, databases, and services. Two case studies were selected to test functionalities of CIWS, including push and pull data models within single family and multi-unit residential contexts, respectively. CIWS was tested for scalability and performance within our design constraints and proved to be effective within both case studies. All CIWS elements and the case study data described are freely available for re-use. Highlights: A complete residential water use cyberinfrastructure demonstration is presented. The system is built using a layered approach with interconnected elements. The open-source technologies used are available for re-use. All steps from data collection to analysis are encompassed in the system. Performance testing demonstrates scalability of the system.